Formation of unilamellar dipalmitoylphosphatidylcholine vesicles promoted by Ca2+ ions: A small-angle neutron scattering study. Issue 1 (2007) - Uhríková Uhríková, Daniela Daniela; Teixeira Teixeira, José José; Lengyel Lengyel, Adrián Adrián; Almásy Almásy, László László; Balgavý Balgavý, Pavol Pavol
Abstract : Dipalmitoylphosphatidylcholine (DPPC) was hydrated in 0.2–60 mM solution of CaCl2 in heavy water and thoroughly homogenized by freezing-thawing process. Small-angle neutron scattering (SANS) shows formation of unilamellar vesicles in the range 1–60 mM of CaCl2 . From the Kratky–Porod plot ln [ I(Q)Q 2 ] vs. Q 2 of SANS intensity I(Q) in the range of scattering vectors Q corresponding to the interval 0.001 Å −2 ≤Q 2 ≤0.006 Å −2, the vesicle bilayer radius of gyration Rg and the bilayer thickness parameter dg were obtained. The structure of the bilayer displays different behavior for the gel phase and the liquid-crystalline phase: In the gel phase (at 20°C), the values of dg indicate nonlinear changes in the lipid bilayer thickness, with a maximum at ~5 mM CaCl2 . In the liquid-crystalline phase (at 60°C), the parameter of the lipid bilayer thickness dg =43.2±0.3 Å is constant within the concentration range 1≤ c Ca ≤40 mM. Vesicles prepared at 60 mM CaCl2 show within experimental error, the same values of dg as pure DPPC unilamellar vesicles prepared by extrusion using polycarbonate filter with pores of diameter 500 Å.